Performance of Companies and Controlling Share Ownership on Company Liquidity: Evidence from Emerging Markets - Aulia Asriani Putri; Riki Martusa; Meythi Meythi (Research Synergy Foundation, 2024)
The relationship between the fundamentals of a firm and cash holdings is an interest topic in financial accounting and financial market literature. Adequate cash holdings can lead to higher profits and financial flexibility, allowing companies to take advantage of opportunities. Therefore, the real estate and property sector requires optimal liquidity holdings to avoid losing investment opportunities and achieve organizational goals. This study examines the effect of controlling share ownership and profitability on cash holdings in the corporate sector. Our samples are the real estate and property sub-sector from 2018 to 2021. The study uses quantitative methods with an archival technique from a capital market database. We performed multiple linear regression to test our hypotheses. The findings show that controlling share ownership has a significant influence on cash holdings. However, the profitability impact on cash holding is not supported. Our study has several limitations, i.e., (1) The study focused only on sub-sector real estate and property, and (2) Our sample period was conducted during 2018-2021. Originality/value examines the effect of controlling share ownership and profitability on cash holdings in the corporate sector, with a focus on the real estate and property sub-sector from 2018 to 2021.